Incidence, morbidity and mortality of patients with achalasia in England: findings from a study of nationwide hospital and primary care data. Issue 5 (20th June 2018) - Harvey, Philip R; Thomas, Tom; Chandan, Joht S; Mytton, Jemma; Coupland, Ben; Bhala, Neeraj; Evison, Felicity; Patel, Prashant; Nirantharakumar, Krishnarajah; Trudgill, Nigel J
Abstract : Background: Achalasia is an uncommon condition characterised by failed lower oesophageal sphincter relaxation. Data regarding its incidence, prevalence, disease associations and long-term outcomes are very limited. Methods: Hospital Episode Statistics (HES) include demographic and diagnostic data for all English hospital attendances. The Health Improvement Network (THIN) includes the primary care records of 4.5 million UK subjects, representative of national demographics. Both were searched for incident cases between 2006 and 2016 and THIN for prevalent cases. Subjects with achalasia in THIN were compared with age, sex, deprivation tand smoking status matched controls for important comorbidities and mortality. Results: There were 10 509 and 711 new achalasia diagnoses identified in HES and THIN, respectively. The mean incidence per 100 000 people in HES was 1.99 (95% CI 1.87 to 2.11) and 1.53 (1.42 to 1.64) per 100 000 person-years in THIN. The prevalence in THIN was 27.1 (25.4 to 28.9) per 100 000 population. Incidence rate ratios (IRRs) were significantly higher in subjects with achalasia (n=2369) compared with controls (n=3865) for: oesophageal cancer (IRR 5.22 (95% CI: 1.88 to 14.45), p<0.001), aspiration pneumonia (13.38 (1.66 to 107.79), p=0.015), lower respiratory tract infection (1.33 (1.05 to 1.70), p=0.02) and mortality (1.33 (1.17 to 1.51), p<0.001). The median time from achalasia diagnosis to oesophageal cancer diagnosis was 15.5 (IQR 20.4) years. Conclusion: The incidence of achalasia is 1.99 per 100 000 population in secondary care data and 1.53 per 100 000 person-years in primary care data. Subjects with achalasia have an increased incidence of oesophageal cancer, aspiration pneumonia, lower respiratory tract infections and higher mortality. Clinicians treating patients with achalasia should be made aware of these associated morbidities and its increased mortality.